2016
DOI: 10.1097/aap.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

The Nerves of the Adductor Canal and the Innervation of the Knee

Abstract: The results suggest that both the SN and NVM contribute to the innervation of the anteromedial knee joint and are therefore important targets of adductor canal block. Given the site of exit of both nerves in the distal third of the adductor canal, the midportion of the adductor canal is suggested as an optimal site of local anesthetic administration to block both target nerves while minimizing the possibility of proximal spread to the femoral triangle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(164 citation statements)
references
References 28 publications
6
139
2
10
Order By: Relevance
“…The findings from this small cadaveric study suggest that a distal AC block may miss the NVM and likely result in suboptimal analgesia compared with more proximal injections. This is in keeping with the findings by Burckett-St Laurant et al who recommended an injection in the mid-AC as a means to block both the SN and NVM 6. The converse argument would contend that injectate placed within the distal AC could avoid blocking the NVM as an advantage to prevent VMM weakness while still blocking the SN with its infrapatellar branch and the subsartorial plexus.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The findings from this small cadaveric study suggest that a distal AC block may miss the NVM and likely result in suboptimal analgesia compared with more proximal injections. This is in keeping with the findings by Burckett-St Laurant et al who recommended an injection in the mid-AC as a means to block both the SN and NVM 6. The converse argument would contend that injectate placed within the distal AC could avoid blocking the NVM as an advantage to prevent VMM weakness while still blocking the SN with its infrapatellar branch and the subsartorial plexus.…”
Section: Discussionsupporting
confidence: 83%
“…Burckett-St Laurant et al found 100% of the intramuscular NVM branches and 35% of extramuscular branches within the AC 6. In contrast, Horner and Dellon describe the NVM to be within the VMM belly in 90% of subjects throughout the AC 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area can be sonographically identified as the midpoint of the proximal and distal ends of the canal. At this site both adductor longus and magnus form medial border of the canal, sartorius forms the roof and the saphenous nerve lies anterolateral to the artery [30].…”
Section: Adductor Canal Blockmentioning
confidence: 99%
“…Sensation over the medial aspect of the knee is by the infrapatellar branch of the saphenous nerve [28,36]. Sensation over the areas of knee is by the peripatellar plexus comprising branches of the femoral and lateral femoral cutaneous nerves [28,35].…”
Section: Innervationmentioning
confidence: 99%